The Impact of Media Consumption Intensity on The Dynamics of Public Opinion Formation Among Generation Z - suci zuriati; Miftakhul Khoiri; Norma Amaliyah; Putri Maharani Yuniza; Azmi Alfaiz Nur (Indonesian Journal of Communication and Social, 2025)
The purpose of this study is to measure the extent to which the intensity of media consumption influences the formation of public opinion among Gen Z. Through a survey of several Gen Z respondents, it was found that the higher the intensity of media consumption, the stronger the influence on opinion formation. Social media was found to be the most important platform for shaping public opinion among Generation Z. The study also identified other factors that moderate the relationship, such as digital literacy and trust in information sources. This research uses a quantitative approach with a survey design. This research has important practical implications for various parties, including policy makers, media industry players and educators. The findings show that Generation Z is highly susceptible to the influence of social media in forming opinions. In addition, the results of this study highlight the importance of media literacy in dealing with the rapid flow of information in the digital age.  It is therefore important for policymakers to develop better regulation of social media content. For media industry players, the results of this study can be used as a reference to develop more effective communication strategies. Meanwhile, educators need to equip young people with adequate media literacy skills to be critical consumers of information.